2001
DOI: 10.1902/jop.2000.72.9.1254
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Within Healthy and Diseased Human Gingiva

Abstract: Human leptin is present within healthy and marginally inflamed gingiva and decreases in concentration as the adjacent probing depth increases. When leptin concentrations decreased (> or =3 mm sulcus), VEGF concentrations increased, suggesting that leptin could be released from gingiva coincident to vascular expansion. Thus, gingiva, in addition to adipose tissue, could be a source of circulating leptin in patients with periodontal disease. This possibility requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
104
1
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(122 citation statements)
references
References 14 publications
12
104
1
5
Order By: Relevance
“…This shows that there is a strong negative correlation between the GCF leptin concentration and periodontal disease progression. The results obtained from our study were in accordance with the study done by Johnson and Serio, 4 who also showed that leptin concentration is correlated negatively with the probing pocket depth. Further, mean serum leptin concentration in healthy group was 8,715.09 pg/ml, in gingivitis group was 10,694.01 pg/ml and in periodontitis group was 12,086.57 pg/ml.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This shows that there is a strong negative correlation between the GCF leptin concentration and periodontal disease progression. The results obtained from our study were in accordance with the study done by Johnson and Serio, 4 who also showed that leptin concentration is correlated negatively with the probing pocket depth. Further, mean serum leptin concentration in healthy group was 8,715.09 pg/ml, in gingivitis group was 10,694.01 pg/ml and in periodontitis group was 12,086.57 pg/ml.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that the leptin is present within the healthy gingiva and its concentration declines coincident to the severity of gingival inflammation and periodontal pocket formation. 4 However, in their study no attempts were made to estimate serum leptin concentration so as to know its correlation with gingival leptin concentration. Hence, the present study was undertaken, which is to assess the concentration of human leptin levels in GCF and serum from healthy periodontium, gingivitis and chronic periodontitis patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24] The presence of leptin has been reported in inflamed and healthy gingival tissues. 25 Leptin concentration is a Postgraduate student, Department of Orthodontics and Dentofacial Orthopedics, Sri Ramachandra University, Chennai, Tamil Nadu, India.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity affects host immunity (19), and the relationship between adipose tissue and the immune system is believed to be related to the secretion of numerous adipokines, including leptin, whose amount is correlated with fat mass (20). It has been demonstrated that human leptin is present within healthy and marginally inflamed gingiva, and decreases in concentration with increased probing depth (21). Recent studies have indicated that adipose tissue, especially visceral adipose tissue, is an important organ that secretes several bioactive substances known as adipocytokines, which include tumor necrosis factor-α, which may enhance periodontal degradation (7).…”
Section: Introductionmentioning
confidence: 99%